2003
DOI: 10.1034/j.1600-0579.2003.00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of video‐based teaching in paediatric dentistry by undergraduate dental students

Abstract: Five cohorts of undergraduate students (n = 160) were filmed on video tape while performing paediatric treatments. Sequences of these recordings were shown 1 day later and discussed. Thus, within one term each student was able to view himself as well as fellow students on video. After the completion of the clinical course in paediatric dentistry, students were asked by means of a questionnaire about the acceptance and benefits of video-based teaching in paediatric dentistry. 95.5% welcomed the use of video in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…When students in the intervention group were asked whether they liked the VCs as a teaching method, all students responded positively. A similar finding was reported in a previous study, which reported very high acceptance of video for teaching in paediatric dentistry by undergraduate dental students . The questionnaires were completed anonymously in the hope that this would encourage the students to response truthfully to the questions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When students in the intervention group were asked whether they liked the VCs as a teaching method, all students responded positively. A similar finding was reported in a previous study, which reported very high acceptance of video for teaching in paediatric dentistry by undergraduate dental students . The questionnaires were completed anonymously in the hope that this would encourage the students to response truthfully to the questions.…”
Section: Discussionmentioning
confidence: 99%
“…At least one study involving undergraduate dental students has reported that the use of video enhanced learning and increased the students’ confidence in dealing with anxious children . There is also evidence to suggest that the acceptance of video for teaching in paediatric dentistry by undergraduate dental students is high …”
Section: Introductionmentioning
confidence: 99%
“…(19)(20)(21). It has also been shown to have beneficial effects for the development of interpersonal and communication skills especially in demanding psychological situations (22).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kneebone (Kneebone et al ., 2002, 2005, Bjork (Bjork & Kirkevold, 2000) and Kalwitzki (Kalwitzki et al ., 2003) all used at least two fixed cameras with associated sound, remote monitors and remote control systems. This amounts to quite a lot of cumbersome and expensive equipment and it is easy to see how it might be much easier to equip a simulation suite with it than to try to create and secure a semi-permanent installation in a busy public ward.…”
Section: How Video Is Used In Health-care Educationmentioning
confidence: 96%
“…The proposition behind most of the published work found was that the educational process is enhanced if individual students have the opportunity to watch themselves in action performing some procedure and then to reflect on their performance. This can be interpersonal (Crute et al ., 1989;Mallett, 1990;Burnard, 1991;Minardi & Ritter, 1999;Pinsky & Wipf, 2000) or technical (Kneebone et al ., 2002(Kneebone et al ., , 2005Kalwitzki et al ., 2003) or both. For example, in a study involving dental students, Kalwitzki found that the students tended to select the more personally challenging rather than technically challenging examples as subjects for review (Kalwitzki et al ., 2003).…”
Section: How Video Is Used In Health-care Educationmentioning
confidence: 97%